KEAP1 Mutations Drive Tumorigenesis by Suppressing SOX9 Ubiquitination and Degradation. Issue 21 (27th September 2020) - Shao, Na; Huang, Hong; Idris, Muhammad; Peng, Xu; Xu, Feng; Dong, Shiwu; Liu, Chungang
Abstract: The transcription factor SOX9 is frequently amplified in diverse advanced‐stage human tumors. Its stability has been shown to be tightly controlled by ubiquitination‐dependent proteasome degradation. However, the exact underlying molecular mechanisms remain unclear. This work reports that SOX9 protein abundance is regulated by the Cullin 3‐based ubiquitin ligase KEAP1 via proteasome‐mediated degradation. Loss‐of‐function mutations in KEAP1 compromise polyubiquitination‐mediated SOX9 degradation, leading to increased protein levels, which facilitate tumorigenesis. Moreover, the loss of critical ubiquitination residues in SOX9, by either a SOX9 (ΔK2) truncation or K249R mutation, leads to elevated protein stability. Furthermore, it is shown that the KEAP1/SOX9 interaction is modulated by CKI γ ‐mediated phosphorylation. Importantly, it is demonstrated that DNA damage drugs, topoisomerase inhibitors, can trigger CKI activation to restore the KEAP1/SOX9 interaction and its consequent degradation. Collectively, herein the findings uncover a novel molecular mechanism through which SOX9 protein stability is negatively regulated by KEAP1 to control tumorigenesis. Thus, these results suggest that mitigating SOX9 resistance to KEAP1‐mediated degradation can represent a novel therapeutic strategy for cancers with KEAP1 mutations. Abstract : This work reports that the Cullin 3 KEAP1 E3 ubiquitin ligase plays a critical tumor‐suppressive role in lung cancer and liver cancer by negatively controlling SOX9 stability. Therefore, either KEAP1 or SOX9 mutation can lead to elevated SOX9 protein levels by evading the KEAP1‐mediated degradation pathway to promote tumorigenesis.